Effect of luteal phase support after ovulation induction and intrauterine insemination. (December 2014) - Oktem, Mesut; Altinkaya, S. Ozlem; Yilmaz, Setenay Arzu; Bozkurt, Nuray; Erdem, Mehmet; Erdem, Ahmet; Gumuslu, Seyhan
Abstract Objective: This study aimed to evaluate the effect of luteal phase support on clinical pregnancy and live birth rates after ovulation induction and intrauterine insemination (IUI). Methods: 579 cycles from 2010 to 2013 were retrospectively evaluated. Ovarian stimulation was performed with gonadotropins, and rHCG was used for ovulation triggering. All patients received IUI. 451 cycles were supported by receiving vaginal micronized progesterone capsules (142 cycles) or vaginal progesterone gel (309 cycles) whereas 128 cycles were not supported. Results: Clinical pregnancy (20.6 versus 9.4%; p = 0.004) and live birth rates (14 versus 7%; p = 0.036) were higher for supported group than for unsupported group. Progesterone gel and micronized progesterone subgroups achieved similar clinical pregnancy and live birth rates (21.4 versus 19%, p = 0.567 and 14.2 versus 13.4%, p = 0.807; respectively). Conclusions: Luteal phase support improved the success of IUI cycles affecting both clinical pregnancy and live birth rates when gonadotropins were used for ovulation induction. The use of vaginal progesterone gel or micronized progesterone significantly improves clinical pregnancy rates. The live birth rates were higher in the progesterone gel group, but were similar in the micronized progesterone group compared to the unsupported group.